Bioorthogonal Reaction Pairs Enable Simultaneous, Selective, Multi-Target Imaging - Karver, Mark R. (2011)
[Image: see text] Mutually orthogonal tetrazine–transcyclooctene and azide–cyclooctyne cycloaddition reactions were used simultaneously for the bioorthogonal labeling of two different live cell populations in the same culture. These small-molecule probes show good chemical reactivity and can be readily incorporated into biological systems.